2020
DOI: 10.1007/s00268-020-05522-1
|View full text |Cite
|
Sign up to set email alerts
|

Should We Consider the Resected Lung Volume in Primary Spontaneous Pneumothorax?

Abstract: Background Although bullectomy is the most curative treatment in primary spontaneous pneumothorax (PSP), postoperative recurrence is not uncommon. New bulla formation at the staple line is the most common cause of recurrence. However, the mechanism is not known. We believe that the pressure gradient plays the main role in new bulla formation. A large resection amount induces a prolonged pressure gradient for obliteration of the residual space. This study aimed to identify the association between resected lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Fifteen studies ( 27 - 30 , 32 - 39 , 41 - 43 ) reported the sex of patients; of a total of 4,128 patients (female: n=601; male: n=3,527), 384 experienced recurrence. The forest plot for sex revealed a significant OR of 0.61 (95% CI: 0.41–0.92; P=0.02) with non-significant heterogeneity (I 2 =0%; P=0.74) ( Figure 6 ) and an asymmetrical funnel plot in the appendix available at https://cdn.amegroups.cn/static/public/jtd-24-175-1.docx .…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies ( 27 - 30 , 32 - 39 , 41 - 43 ) reported the sex of patients; of a total of 4,128 patients (female: n=601; male: n=3,527), 384 experienced recurrence. The forest plot for sex revealed a significant OR of 0.61 (95% CI: 0.41–0.92; P=0.02) with non-significant heterogeneity (I 2 =0%; P=0.74) ( Figure 6 ) and an asymmetrical funnel plot in the appendix available at https://cdn.amegroups.cn/static/public/jtd-24-175-1.docx .…”
Section: Resultsmentioning
confidence: 99%
“…It is usually achieved by stapling or sectioning the lung parenchyma with an automatic forceps. In the absence of a detectable lesion, an atypical parenchymal resection at the apex may be performed [ 156 ], contributing to subsequent pleurodesis, and allowing pathological analysis of the underlying lung. The use of aerostatic material has been suggested in order to cover the stapling line, to reduce the risk of recurrence [ 157 ].…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…16,17) They suggested that the resected lung volume influenced the recurrence of PSP. 18,19) It is reasonable to hypothesize that lung deformation following large lung resection and high pressure at lung expansion on the stapling lines induced NOB. It is easy to imagine that the middle part of the stapling will be exposed to high pressure at lung expansion in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%